REFORMASI PENDIDIKAN AGAMA DI ERA MODERN UNTUKMEWUJUDKAN MASYARAKAT MADANI - Saefur Rochmat (Jurnal Cakrawala Pendidikan, 2002)
Refonnation in education on religion should start with a fundamental change in the philosophy of religious education in thecontextofIndonesia by constructing a system ofreligious education suitable for modem society and ableto counter the negative impactsofmodem civilization. Cooperation and coordination among religions are required to refonnulate the vision,mission,strategy, and operational techniques ofreligious education. We should change the approach to religious education fromthe theologically minded one into that based on ethics in orderthat dialogical communication among religions and even different sects within religions is made possible.John Naisbitt's and Patricia Aburdane's predictionofa religious awakening in the21" century still needs considerable evidence to support its validity. The numberofreligious followershas indeed increased but practice in religious teachings is still oflow quality so that the increase has not significantly contributedto the fulfillmentofthe aspect ofsalvation in life in the fonn ofjustice, welfare, security, and consistence oflaw. The riots thathave broken out since early 1998 have also soiled the imageofreligion. The material aspects ofmodem or Western civilizationstill impress many and particularly those belonging to theyounger generation who are yet to find their identity. The Westhas become more confident in claiming its way as the way to thesalvation after the fallofthe Berlin wall, which has been a symbolofthe supremacy ofcommunism, in spite ofthe shOCk felt byboth the Western and Eastern blocs when the Islamic revolutionin Iran led by someone considered traditional succeeded in toppling the ruling Reza Pahlevi.Indonesia can be considered a state which is still faithful toreligion because no Indonesian is willing tobe called an atheistthough he is a communist. Indonesia can also be considered theworld's greatest Islamic state because its number ofIslamic followers is the largest in any country the world. Consequently,Islamic followers have a significant role in establishing salvation in life. Thath\ls also been the reason why the aforementioned riots have affected Islam's image. But it has not stoppedwith Islam.It has also reflected on other religions, blamed forbeing unable to bring salvation in life and, moreover, for beingunableto become an alternative to materialistic modem society.The solution is a religious education which is more ethics-basedin approach rather than solely theological